Prevalensi Kecenderungan Social Withdrawal (Hikikomori) pada Remaja di Kota Bandung - Wini Resna Novianti; Windy Rachmawati; Titin Sutini (Jurnal Keperawatan Silampari, 2023)
This study aims to describe the tendency of social withdrawal (Hikikomori) in adolescents. The research method used in this research is descriptive quantitative. The results showed that almost half of the respondents tended to experience social withdrawal (Hikikomori) 40%, and most of the samples experienced a low-level tendency of 66 models (60%). In conclusion, most respondents have a low social withdrawal tendency (Hikikomori). Keywords: Hikikomori, Social Withdrawal